Morlille kan ikke flyve: Natursproglig semantik og datamater - Prebensen, Henrik (Psyke & Logos, 2023)
This paper deals with natural language (NL) semantics an the computer. It presents two major theoretical vicwpoints in linguistic semantics: representational and denotational. In linguistic theory, these two issues are mostly understood as mutually exclusive, as can be seen from Chomskyan and Montague Grammar. The paper discusses representational semantics in connection with the autonomous syntax approach of mainstream transformational grammar, denotational semantics in connection with the model-theoretic approach of Montague grammar. In the next step, I consider the implementation of model-theoretic NL comprehension systems on the computer. In the present context, they are viewed principally as a means to make experimental studies in the formalizations of NL. It is shown that the correct handling of referential NL terms in such systems can be achicved only if these systems combine methods and techniques from both types of semantics. Finally, the cognitive meaning of the concept of computer understanding is touched upon.